Applying cognitive informatics to improve communication in geographically distributed environments - Aranda, Gabriela N. (2004)
When stakeholders are geographically distributed, elicitation process becomes more difficult and communication between all the participants presents new challenges for software engineering community. Considering characteristics of interpersonal communication and the virtual area where it is carried out, we aim at improving the quality of elicitation results by applying concepts from a new transdisciplinary science called Cognitive Informatics.